Effect of MTA-based sealer on the healing of periapical lesions - Gomes Filho, João Eduardo [UNESP]; Watanabe, Simone [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Nery, Mauro Juvenal [UNESP]; Dezan Junior, Eloi [UNESP]; Queiroz, India Olinta Azevedo [UNESP]; Lodi, Carolina Simonetti [UNESP]; Basso, Maria Daniela [UNESP] (My University, 2013)
Some manufacturers have recently added specific components to improve the ease of handling and insertion material properties of MTA in order to create MTA-based sealers. Objective: The aim of this study was to evaluate the healing of periapical lesions in canine teeth after a single session of endodontic treatment with MTA Fillapex® compared with Sealapex® or Endo-CPM-Sealer®. Material and Methods: Sixty-two root canals were performed on two 1-year-old male dogs. After coronal access and pulp extirpation, the canals were exposed to the oral cavity for 6 months in order to induce periapical lesions. The root canals were prepared, irrigated with a solution of 2.5% sodium hypochlorite and filled with gutta-percha and different sealers, according to the following groups: 1) Sealapex®; 2) Endo-CPM-Sealer®; and 3) MTA Fillapex®. Some teeth with periapical lesions were left untreated for use as positive controls. Healthy teeth were used as negative controls. After 6 months, the animals were sacrificed and serial sections from the roots were prepared for histomorphologic analysis and stained with hematoxylin and eosin and the Brown and Brenn technique. The lesions were scored according to pre-established histomorphologic parameters and the scores statistically analyzed using the Kruskal-Wallis test. Results: All 3 materials produced similar patterns of healing (p>0.05); in particular, persistent inflammation and absence of complete periapical tissue healing were consistently noted. Conclusions: Preparation of the infected root canals followed by filling with the materials studied was insufficient to provide complete healing of the periapical tissues.
Keywords: Dental materials; Endodontics; Material testing